Association of age at menarche, parity, and hormonal contraceptive use with the histologic type of ovarian cancer - Firda Azizah; Pungky Mulawardhana; Willy Sandhika (Universitas Airlangga, 2021)
HIGHLIGHT1. Relationship between age at menarche, parity, and contraceptive use with histologic type of ovarian cancer was analyzed. 2. A number of patients with ovarian cancer were analytically observed with retrospective cross-sectional approach and the histologic types of the cancer were determined.3. Age of menarche, parity, and hormonal contraceptive use was found not to have significant correlation with histologic type of ovarian cancer. ABSTRACTObjectives: This study analyzed the relationship between age at menarche, parity, and contraceptive use with histologic type of ovarian cancer.Materials and Methods: This study used an observational analytic with a retrospective cross-sectional approach. The research samples were 128 patients with ovarian cancer at Dr. Saiful Anwar Hospital, Malang, Indonesia, in 2017-2019. All patients underwent primary staging laparotomy. The histologic types of the ovarian cancer consisted of serous type as many as 45, mucinous 45, endometrioid 10, clear cell 20, and others 4. Data analysis used chi-square test.Results: The p value for the relationship between age of menarche and histologic type of ovarian cancer was p=0.500 (p> 0.05), parity p=0.313, and contraceptive use p=0.824. The distribution of clear cell was more common in multiparous, 40% of endometrioid found in nulliparous, while serous were more common in women with hormonal contraceptive use >5 years, whereas mucinous were more common in those with history of use of <5 years.Conclusion: There was no significant relationship between age of menarche, parity, and hormonal contraceptive use on histologic type of ovarian cancer.